2022
DOI: 10.1177/00400599211066914
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Transition-Age Students to Use Self-Determination Assessment to Lead IEP Goal Development

Abstract: Self-determination is a predictor of positive in- and post-school outcomes, including access to general education, competitive employment, and community participation. Emerging research has focused on promoting self-determination for all students given alignments with college and career readiness frameworks and equity-based education. However, it is also important to enhance self-determination as students participate in the Individualized Education Program (IEP) goal development process. Empowering transition-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Fortunately, educators found that the SDLMI provided opportunities to enhance collaboration. In reflecting on the role of general and special education in supporting student success, general and special educators agreed they shared a common goal and saw the SDLMI as a potential avenue for connecting instruction that occurred in general and special education settings, including IEP goal development (Raley et al, 2022). Evelyn emphasized that all teachers were responsible for all students, saying, “I think we’re all here for student success, in that all students are all our students, not just [special] or [general education].…”
Section: General and Special Educator Tips For Promoting Self-determi...mentioning
confidence: 99%
“…Fortunately, educators found that the SDLMI provided opportunities to enhance collaboration. In reflecting on the role of general and special education in supporting student success, general and special educators agreed they shared a common goal and saw the SDLMI as a potential avenue for connecting instruction that occurred in general and special education settings, including IEP goal development (Raley et al, 2022). Evelyn emphasized that all teachers were responsible for all students, saying, “I think we’re all here for student success, in that all students are all our students, not just [special] or [general education].…”
Section: General and Special Educator Tips For Promoting Self-determi...mentioning
confidence: 99%
“…The first lesson supports students to learn about their current level of self-determination measured by the Self-Determination Inventory: Student Report (SDI:SR). The SDI:SR is a validated transition assessment and can be used as a formal transition assessment to inform PLAAFPs, postschool goals, and transition activities and services (Raley et al, 2022). After students complete the SDI:SR, they receive a report that describes their scores across three self-determined actions, DECIDE, ACT, and BELIEVE (Shogren et al, 2015, 2019).…”
Section: Implementing the Sdlmi In Transition Planning Contextsmentioning
confidence: 99%
“…Have students review this report as it supports them in identifying their strengths and areas of growth, identifying goals, creating action plans, and deciding next steps. Encourage students to discuss what each of these self-determined actions means to them and their family based on cultural identities (Raley et al, 2022). Then, students learn about goals (Preliminary Conversations 2), the differences in long and short-term goals (Preliminary Conversations 3), and the SDLMI, teacher and student roles and responsibilities, and key terms that will support them in navigating the process (Preliminary Conversations 4; Burke et al, 2020).…”
Section: Implementing the Sdlmi In Transition Planning Contextsmentioning
confidence: 99%
“…Educators have reported that students who lead their IEP meetings have a better understanding of their personal strengths and limitations and have greater knowledge of their rights and the resources that are available to them (Mason et al., 2004). Participation in the IEP process provides students with an opportunity to practice advocating for their needs, preferences and supports – skills that are certainly important, especially as students prepare for increased independence in adulthood (Raley, Hagiwara and Shogren et al., 2022).…”
Section: Introductionmentioning
confidence: 99%